2022
DOI: 10.1186/s43045-022-00219-8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of problematic Internet use and its correlates among Egyptian adolescent students in international schools in Cairo

Abstract: Background Internet addiction is a global phenomenon that has been a topic of great interest to researchers, clinicians, teachers, parents, and community groups. The study aims in determination of the rate of problematic Internet use among a sample of Egyptian adolescent students, relations of problematic Internet use with socio-demographic data, risk factors, and comorbid psychiatric disorders. A sample of 248 Egyptian adolescent school students aged 11 to 18 years old were assessed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The research on teenagers and IA shows that IA can lead to bad habits (eating disorders, work, and rest disorders, smoking, etc. ), decreased academic performance (reduced attention and memory), and anxiety and depression in some mental diseases [ 6 , 7 ]. And with time, non-suicidal self-injury and suicidal ideation of teenagers with Internet addiction showed an upward trend [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research on teenagers and IA shows that IA can lead to bad habits (eating disorders, work, and rest disorders, smoking, etc. ), decreased academic performance (reduced attention and memory), and anxiety and depression in some mental diseases [ 6 , 7 ]. And with time, non-suicidal self-injury and suicidal ideation of teenagers with Internet addiction showed an upward trend [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous researchers' work reported that there was a prevalence of 33% for PIU among Spanish adolescents [3]. A survey in Egypt has found that 35.1% of adolescents suffer from moderate Internet addiction, and 3.6% suffer from severe addiction [4]. Several studies have suggested there are harmful effects of PIU on adolescents' physiological, physical, psychological, and behavioural development, such as gray matter abnormalities, vision loss, depression, and sleep disturbances [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%